HUBUNGAN KEBERADAAN ORANG TUA DI RUMAH TERHADAP MOTIVASI BELAJAR SISWA KELAS IX SMPN 2 LEMBANG - Mispa Caroline Tambunan; Nisrina Nur Arifah Angga Riyana; Ratih Pitria Nurazizah; Talitha Diva Sadina; Ibrahim Al Hakim (Jurnal Sosial Humaniora dan Pendidikan, 2024)
Parental involvement contains an exceptionally imperative part in expanding students' learning motivation, particularly amid youth, where academic pressures are often accompanied  by emotional instability. This considers points to examine the relationship between parental nearness at home and the learning inspiration of grade IX students at SMPN 2 Lembang.Utilizing expressive quantitative strategies, information was collected through surveys conveyed to 267 respondents, representing 80.36% of all grade IX students. The main variables analyzed include the frequency and duration of parental presence as well as indicators of student learning motivation, such as achievement goals, engagement, and academic success. The study used Pearson correlation analysis to investigate the connection among these variables. The findings indicated a strong positive correlation (r = 0.776) between parental presence and overall learning motivation, with a stronger relationship (r = 0.791) in students living with their parents compared to those not living with their parents (r = 0.327). Students who live with their parents tend to be more motivated because they receive direct emotional and academic support at home. In contrast, those who do not live with their parents tend to draw motivation, such as other family members or peers.This research emphasizes the importance of parental involvement in improving students' learning motivation while highlighting other factors such as socioeconomic status, parents' education level and the quality of the parent-child relationship. Additionally provides practical recommendations, such as increasing parental involvement through school programs and providing additional support for students who do not live with their parents.